"It's my business, it's my body, it's my money": experiences of smokers who are not planning to quit in the next 30 days and their views about treatment options. (December 2016) - Bartlett, YK; Gartland, N.; Wearden, A.; Armitage, CJ; Borrelli, B.
Abstract Background Current evidence-based smoking cessation treatments in the UK are only offered to smokers ready to quit within 30 days. This study reports the experiences of smokers who are not ready to quit and explores the types of intervention approaches that might engage them. Methods Five focus groups were conducted with smokers who had no plans to quit within 30 days (n = 32, 44 % female). Verbatim transcripts were analyzed thematically using Nvivo 10 software. Results Participants were ambivalent towards their own smoking, but the majority indicated they would like to quit someday. Smoking was seen both to hinder and facilitate social interactions, depending on the social norms of the participant's social circle. Participants reported that, when they perceive pressure to quit smoking, they respond defensively; concurrently, existing approaches to encouraging smoking cessation were seen as unappealing. In contrast, the importance of intrinsic motivation to quit was emphasized, and interventions that were tailored, increased intrinsic motivation and kept the smoker engaged in activities incompatible with smoking were preferred. Conclusions Despite not planning to quit in the next 30 days, the majority of participants wanted to quit smoking at some point. Even if existing services were offered to smokers not planning to quit in the next 30 days, it is unlikely that these services would meet the needs of this population. Future research should explore novel approaches to appeal specifically to smokers not planning to quit in the next 30 days, such as encouraging engagement with activities incompatible with smoking and fostering non-smoking habits.